Studi Eksperimental Analisis Pengaruh Serbuk Cangkang Bekicot dan Bakteri Bacillus Subtilis pada Tanah Lunak Terhadap Nilai Kepadatan dan Kuat Tekan Tanah di Kecamatan Wonoayu - Sidoarjo - Divia Rahma Putri; Laily Endah Fatmawati; Andi Patriadi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effect of adding snail shell powder and Bacillus subtilis bacteria on the physical and mechanical properties of clay soil in Wonoayu District, Sidoarjo. Based on the USCS classification, the original soil was categorized as OH soil with high plasticity and low bearing capacity. Laboratory tests conducted in this study included water content, volumetric test, specific gravity, Atterberg limits, Proctor test, and Unconfined Compression Strength (UCS). The mixtures used consisted of 5%, 10%, and 15% snail shell powder combined with 6% Bacillus subtilis and cured for 7 days. The results showed that the stabilization process reduced water content, void ratio, degree of saturation, and soil plasticity values. The maximum dry density increased from 1.447 gr/cm³ to 1.536 gr/cm³, while the highest UCS value was obtained in the 15% SCB + 6% BS mixture at 0.53108 kg/cm². These results indicate that the combination of snail shell powder and Bacillus subtilis effectively improves the stability and strength of clay soil.